'Cry‐for‐help' in contaminated soil: a dialogue among plants and soil microbiome to survive in hostile conditions. (23rd June 2021) - Rolli, Eleonora; Vergani, Lorenzo; Ghitti, Elisa; Patania, Giovanni; Mapelli, Francesca; Borin, Sara
Summary: An open question in environmental ecology regards the mechanisms triggered by root chemistry to drive the assembly and functionality of a beneficial microbiome to rapidly adapt to stress conditions. This phenomenon, originally described in plant defence against pathogens and predators, is encompassed in the 'cry‐for‐help' hypothesis. Evidence suggests that this mechanism may be part of the adaptation strategy to ensure the holobiont fitness in polluted environments. Polychlorinated biphenyls (PCBs) were considered as model pollutants due to their toxicity, recalcitrance and poor phyto‐extraction potential, which lead to a plethora of phytotoxic effects and rise environmental safety concerns. Plants have inefficient detoxification processes to catabolize PCBs, even leading to by‐products with a higher toxicity. We propose that the 'cry‐for‐help' mechanism could drive the exudation‐mediated recruitment and sustainment of the microbial services for PCBs removal, exerted by an array of anaerobic and aerobic microbial degrading populations working in a complex metabolic network. Through this synergistic interaction, the holobiont copes with the soil contamination, releasing the plant from the pollutant stress by the ecological services provided by the boosted metabolism of PCBs microbial degraders. Improving knowledge of root chemistry under PCBs stress is, therefore, advocated to design rhizoremediation strategies based on plant microbiome engineering.